Caracterização biométrica do fruto e avaliação dos efeitos do encapsulamento na estabilidade e bioacessibilidade in-vitro de extratos antociânicos do jambolão (Syzygium cumini L. skeels) - Melo, Filipe de Oliveira (2022)
The consumption of S. cumini (Jambolan) is associated, by folk medicine, with a range of health benefits. Part of these benefits derive from the antioxidant action of anthocyanins in the body. These compounds are extremely sensitive to environmental variations in temperature, pH, light or oxygen, and the ionic gelation encapsulation technique is used to improve their stability. In this sense, the present work sought to identify the variables that directly impact jambolan pulp yield, optimize the encapsulation process of anthocyanins extracted from the fruit by the ionic gelation technique, as well as evaluate the effects of the encapsulation process on stability and bioaccessibility of anthocyanins. The average pulp yield was observed in the order of 65.15±8.57 %, this variable being positively and significantly influenced (p<0.05) by the horizontal diameter (DH) (rS = 0.391) and the fruit weight ( PF) (rS = 0.493), in such a way that the higher the DH, the higher the PF, obtaining higher pulp yield. The encapsulation process was represented by a quadratic model (R2 = 0.9306), and the optimized capsule (CO) (1.25% - starch and 1.81% - inulin) showed an Anthocyanin Encapsulation Efficiency - EEA (%) of 67%. The capsule also showed a high retention (>60%) of Phenolic Compounds (226.61±22.95 mg EAG/100g) and Total Flavonoids (779.14 mg EQ/100g), in addition to preserving the antioxidant capacity of the extract with an ABTS radical scavenging power in the order of 1,335.15 µmol of Trolox equivalent/g (EE (%) – 125.53%) and a reduction capacity of Fe3+ ions in the order of 21,822.42 µmol Fe2SO4/100g (EE ( %) – 97.49%). Scanning Electron Microscopy (SEM) data pointed to a surface effect of agents added to the capsule. It was also observed that the encapsulation process increased the stability of anthocyanins encapsulated and stored both under refrigeration (5°C) and at room temperature (30°C), retaining, at the end, contents higher than 60% of the agent. Finally, in relation to the evaluation of bioaccessibility, determined through the in-vitro digestion process, higher release rates in CO were observed when subjected to simulated gastric fluid (96%), compared to pulp (50% ) and extract (15%), indicating that the type of matrix directly influences the bioaccessibility of the compound. In this sense, there is a high potentiality in the use of the jambolan fruit, appealing mainly to its nutraceutical properties. Furthermore, the use of the ionic gelation technique proved to be an important tool to ensure greater stability, as well as higher rates of release of anthocyanins extracted from jambolan, when subjected to the in-vitro digestion process. It is suggested that further studies be carried out, evaluating the behavior described in in-vivo models, as well as with the capsules arranged in different food matrices.